Multisite Radiotherapy Combined With Tislelizumab for Metastatic Castration-Resistant Prostate Cancer With Second-Line and Above Therapy Failure: Study Protocol for an Open-Label, Single-Arm, Phase Ib/II Study - Cheng, Ke; Wang, Yuqing; Chen, Ye; Zhu, Jingjie; Qi, Xiaohui; Wang, Yachen; Zou, Yanqiu; Lu, Qiuhan; Li, Zhiping (Frontiers in Oncology, 2022)
Background: Tislelizumab combined with radiotherapy as a salvage treatment for patients with end-stage metastatic castration-resistant prostate cancer (mCRPC) is not reorted. This study aimed to describe a protocol to evaluate the safety and efficacy of multi-site radiotherapy combined with tislelizumab as a salvage therapy for mCRPC in patients who had at least one second-line treatment failure. Methods: The study will recruit patients with mCRPC who had at least one lesion suitable for radiotherapy and failed androgen deprivation therapy (ADT), followed by at least one novel second-line endocrine therapy. All patients will receive tislelizumab monotherapy induction therapy for two cycles, then combined with multi-site radiotherapy for one cycle, followed by tislelizumab maintenance therapy, until either disease progresses or develops unacceptable toxicity. Radiation methods and lesions will be individually selected according to the specified protocol. Primary endpoints will include safety and objective response rate. Secondary endpoints will include prostate-specific antigen (PSA) response rate, disease control rate, overall survival, radiographic progression-free survival (rPFS), and biochemical progression-free survival (bPFS). Furthermore, the exploratory endpoints will include the identification of the predictive biomarkers and exploration of the correlation between biomarkers and the tumor response to the combined regimen. Discussion: This study will include three treatment stages to evaluate the efficacy of immunotherapy and the combination of immunotherapy and radiotherapy for patients with mCRPC who had at least second-line treatment failure. Additionally, it will determine radiation-related and immune-related both early and late toxicities, respectively. Furthermore, the study will also aim to identify the predictive biomarkers associated with immunotherapy for treating mCRPC.